Evaluation of primary non-compliance with discharge medication at a private hospital - Kruger, Daniel Frederik (University of Limpopo ( Medunsa Campus), 2009)
ABSTRACT Background: When a patient is discharged from the hospital, the doctor may prescribe medication to be used at home which is called TTO (To Take Out) medication. Failure by the patient to collect TTO medication might be intentional or may indicate a lack of appropriate structures and procedures at the hospital to provide such care on discharge, and/or failure by the health care professionals to reach concordance with the patient to ensure that he/she continues to take medications as prescribed. Objectives: The purposes of this study were to examine the prevalence of primary non-compliance with medication in this private hospital and to explore its association with various factors contributing to its existence. Methodology: The study was conducted at a private hospital in Gauteng, South Africa. The study focused on discharged patients who did not redeem their TTO medication. Thus only patients discharged from the hospital within a thirty day period between 25 May 2009 and 23 June 2009 were included in the study. For each subject the discharge medication prescription was reviewed and the following determined: number of items prescribed, number of items dispensed at the hospital pharmacy, whether any items were non-dispensed, whether any items were partially dispensed and reason for any item non-dispensed or partially dispensed. A telephone call was made to those subjects for whom a discharge medication script was prescribed, but no medication was dispensed at discharge. Information was collected from the patients to identify possible reasons for not redeeming discharge medication. Results: In total 1365 records were evaluated. TTO medication was prescribed for 1161 (85%) patients discharged. All items were redeemed in full by 854 (74%) of the patients, 118 (10%) patients redeemed no discharge medication, 101 (9%) patients redeemed only some items prescribed, 74 (6%) patients redeemed all items partly, 14 (1%) patients redeemed some items partly and some not at all and for seven v patients details were not known. Four reasons and five types of medication together accounted for 54% of the total value not redeemed. The four reasons include the following: medical aid TTO rules, patient unaware of TTO being prescribed, ward stock given, patient still had stock at home, and the types of medication included: blood and haematopoietic agents, analgesics, antimicrobials, agents of the gastrointestinal tract and unclassified. Conclusion: Some patients reported that they took own decision not to redeem the medication and some still had stock at home, a fact that should lead healthcare providers to ensure that they reach concordance with their patients.
Thesis (MSc. (Med.)(Pharmacy))--University of Limpopo, 2009.
Keywords: Prescribed medication; Discharged patients